Rhetoric Style in Taylor Swift’s Back To December - Jati, Ariya (Universitas Muhammadiyah Semarang, 2018)
This study is concerned with how a language of rhetoric is used in the lyric of Taylor Swift‘s Back to December. The study is led by a premise that the language of literature can be found in songs, and the study is carried out to support the premise. The study is intended to depict elements of the language of rhetoric in the lyric in order to designate the style of the lyric. The study takes the lyric as a text, so it voids the music to the lyric. The study applies a textual analysis to the lyric as its research method, and it adopts Chapman‘s concept of stylistic analysis to the lyric as its approach method. The textual analysis involves interpretation of the lyric‘s lines, and the stylistic analysis incorporates linguistic and literary description of the elements of the language of rhetoric. The analyses result in conditional expressions and figurative expressions, comprising imagery, symbol, personification, and irony. In brief, the study is expected to be supplementary to general readership in music and poetry: the lyric is stylistically appealing; it is not only musical, but it is also poetic.